Offertradition og religion i ældre jernalder i Sydskandinavien – med særlig henblik på bebyggelsesofringer - Hansen, Jesper (Kuml, 2006)
Sacrificial Tradition and Religion during the Early Iron Age in South Scandinavia – with Special Reference to Settlement Sacrifices Sacrificial customs and religion during the Early Iron Age (500 BC–400 AD) has occupied archaeologists from the infancy of archaeology. Most would probably agree that the religion was primarily fertility related, originating as it was in the existing peasant society. The literature does not reflect any disagreement about the religion of the Early Iron Age being polytheistic and consequently concerned a variety of gods. However, it is still unknown how the religion was integrated in the everyday life, and under which conditions it was practiced. The research interest and the overall synthesis framework have especially addressed sacrifices in bogs and wetlands (for instance weapon sacrifices, bog bodies, deposited earthenware, anthropomorphic wooden figures, domestic animals, cauldrons, ring sacrifices, etc.). Strongly simplified, the existing consensus may be expressed in one single sentence: The overall society-related sacrificial traditions develop from being almost exclusively connected with wetland areas during the Early Iron Age (until c.400 AD) to being primarily connected with dry land after this time, cf. Fig. 1. The question is whether – based on the intense data collection over the recent decades – archaeology can or should maintain this very simple picture of the development of the sacrificial traditions and the religions during the Iron Age? Is it possible that we – rooted in for instance narrow definitions of sacrificial finds, habitual thinking, and a “delusion” consisting of the numerous well-preserved, well-documented, spectacular, and impressive finds of bog sacrifices – fail to see numerous forms of deposits, which (as opposed to the impressive finds of sacrifices in bogs) are hidden in the archaeological material? The settlements of the Iron Age have been excavated in large numbers over the recent decades, and it is the ritual finds from these localities that provide the background for this article. The ritual deposits from the settlements can be divided into two superior groups distinguished by the physical context. One comprises sacrifices made to constructions, which are characterized by being directly connected to a specific structure; the other encompasses settlement sacrifices that are to a higher degree characterized by an overriding affiliation to the settlement. The establishment of a sacrifice definition suitable for scanning the archaeological material for relevant finds is of vital importance. As the definition should not beforehand restrict the search through the material, it is important not to narrow the basis by concentrating only on the physical characteristics of the individual artefacts. The general idea behind the present presentation is that the different ritual dimensions of a society are internally connected as they function within the same overall conventions and, as a consequence, make up parts of a general mental structure, which can leave physically recognizable traces across the different ritual dimensions, cf. Fig. 2. This principal viewpoint creates a theoretical starting point for my work and the established definition of sacrificial finds: All intentionally deposited objects, which analytically show significant similarities as regards their physical appearance and/or their deposition context with other recognized ritual objects/contexts, and which are closely connected to these in time and space, should, when analysed, be considered sacrificial finds. The British religious historian, Ninian Smart, describes religion as consisting of seven thematically describing situations, which – albeit not completely unconnected – may be described individually: 1) A dogmatic and philosophical dimension, comprising doctrine systems. 2) A mythical and narrative dimension, comprising tales of the deities, of the creation, etc. 3) An ethical and judicial dimension, comprising the consequences of the religion in relation to the shaping of the life of the individual. 4) A social and institutional dimension comprising organisations and institutions that tie together the individual religious society. 5) An empirical and emotional dimension comprising the individual’s experience of god and the divine. 6) A ritual and practical dimension comprising prayer, sacrifices, worship, etc. 7) A materiel dimension comprising architecture, art, sacred places, buildings, and iconography. As archaeologists, we have a very limited possibility of investigating the very thoughts behind the practiced religion. It is therefore natural to concentrate to a higher extent on the overall setting for it – the ritual dimension and the materiel dimension respectively. The ritual dimension and in particular its sacrificial aspect is traditionally divided into groups characterised by their significance level within the religion as such. 1) The first and most “important” group consists of cult rituals. These are characterized by being calendar rites based on the myths of the religion or the history of the people, and by playing a part in the events of the year. 2) The next group comprises transition rites (rite de passage), which follow the life cycle of the individual. 3) The last group comprises rites of crises, which serve the purpose of averting danger, illness, etc. It is important to realize that the two first ritual groups are predictable cyclic rituals addressing the gods, the myths, and/or the people/the individual respectively. Only the third and least central group of rituals is determined by non-predictable and “not-always” occurring incidences. On this background, it becomes central to analyse, which category one is facing when one wants to assess its importance for the religion as such, in order to evaluate the primary character of the religion. In an attempt to understand the overall importance of a specific ritual practice, one cannot ignore a very complicated problem, which is to evaluate whether the sacrifices were practiced by single individuals or by a larger group of people as part of more common and society-supporting rituals. The issue of the relation between different sacrifice types and the groups causing these has been addressed repeatedly. Often, narrow physical interpretation frames as to who sacrificed what are advanced (i.e. Fig. 3). However, the question is how suitable are these very narrow and rigid interpretation models? As mentioned above, a sacrifice is defined by the intention (context) that caused it rather than by the specific physical form of the object! The above mentioned methodical and theoretical issues provide the background for the author’s investigation of the archaeological sources, in which he focused especially on the relationship between ritual actions as they are expressed in bog deposits and in burial grounds and measured them against the contemporary finds from the settlements. The analysis of the archaeological material is based on those find groups (sacrifices of cauldrons, magnificent chariots, humans, animals, metals, and weapons), which have traditionally been presented as a proof that society supporting and more community influenced ritual sacrifices were carried out beside the bogs. The examination of the material supports that sacrifices of cauldrons, magnificent chariots, humans, animals, and earthenware are found in both settlements and wetlands (Figs. 4-12), and that the deposits seem to follow superior ritual conventions, i.e. Fig. 2. The sacrifices were not made in fixed sacred places but in a momentary sacred context, which returns to its daily secular sphere once the rituals have been carried out. Often, the ceremony consists of a ritual cutting up of the sacrificed object, and the pars pro toto principle occurs completely integrated in connection with both burial customs, wetland sacrifice customs, and settlement sacrifice customs. Sacrifices often occur as an expression of a rite de passage connected to the structures, fields, or infrastructure of the village. However, the repeated finds of earthenware vessels, humans, and animals in both wetland areas and in the villages indicates that fertility sacrifices were made regularly as part of the cyclic agricultural world. This places the find groups in a central position when it comes to understanding the religious landscape of the Early Iron Age. In a lot of respects, the settlement finds appear as direct parallel material to the contemporary wetland-related sacrificial custom and so one must assume that major religious events also took place in the settlements, for instance when a human or a cauldron was handed over to the next world. Both the selection of sacrificial objects, the form of depositing, and the preceding ceremonial treatment seem to follow superior ritual structures applying to both funerary rites and wetland sacrifices in Iron Age society. Often, the individual settlement-related sacrificial find seems to be explained by everyday doings, as largely all sacrifice-related objects of the Early Iron Age have a natural affiliation with the settlement and the daily housekeeping. However, it is clear that if the overwhelming amount of data is made subject to a comprehensive and detailed contextual analysis, settlement related find groups and attached action patterns appear, which have direct parallels in the ritual interpretation platform of the bog context. These parallels cannot be explained by pure practical or coincidence-related explanation models! As opposed to ploughed-up Stone Age axe deposits or impressive bronze depots from the Bronze Age and gold depots from the Late Iron Age, a ploughed-up collection of either earthenware, bones, human parts, etc. are not easily explained as sacrificial deposits. However, much indicates that the sacrificial settlement deposits of the Iron Age were not placed very deeply, and so they occur in the arable soil of later times. We must therefore assume that these very settlement-related sacrificial deposits from the Early Iron Age are extremely underrepresented in the available archaeological material. In order to clarify the sacrifice traditions in the Early Iron Age settlements, it is therefore necessary to have localities, which comply with a very rarely occurring find situation. The sites must have fine preservation conditions for bone material and, equally important, thick, continuously accumulated deposits of culture layers, as these preserve the usually shallowly deposited sacrifices. Further, it would be a great advantage if the site has a high degree of settlement continuity, as under optimal conditions, the investigation should comprise the activities of several centuries on the same spot. The Aalborg area holds Early Iron Age localities, which meet all of the above-mentioned conditions – for instance the settlement mound of Nr. Tranders, from which a few results will be pointed out. Time wise, the locality covers all of the Pre-Roman Iron Age and the fist part of the Early Roman Iron Age. Around ten farm units have been excavated from the settlement, each of which can be traced across a period of several hundred years. The houses were constructed with chalk floors (cf. Fig. 13), which give optimal preservation conditions for bone material, and the culture deposits assumed a thickness of up to 2 metres. Around 150 houses were excavated at this site (cf. Fig. 14). The author systematically checked the comprehensive find material, and starting from the theoretical and methodical approach presented in this article, was able to isolate 393 sacrificial deposits – a very comprehensive material in comparison with the sacrificial wetland sites! In 279 cases, it was possible to isolate sacrifices in connection with constructions. These comprised such different items as Stone Age axes, fossils, dress pins, a bronze fibula, iron knives, iron arrowheads, a bronze ring, an iron axe, various pottery sacrifices, amber, bone stilettos, bone spearheads, a bone arrowhead, complete animal skeletons, animal skulls and jaws, various animal bones, an infant, humane skull fragments, etc. (cf. Fig. 15). Just as the sacrificed objects themselves vary, so does the sacrifice intensity in the different constructions. Thus, houses without any registered construction sacrifices occur, whereas other constructions showed up to 5-15 sacrifices. These intense sacrifice activities are mainly connected with the later settlement phases from the Late Pre-Roman and the Early Roman Iron Age. The most ordinary find groups are different animal bones, pottery, Stone Age axes, fossils, and various pointed or edged tools. It is a characteristic of the construction sacrifices that they almost never show any signs of having been burnt prior to the depositing. The fact that all finds are not comparable merely because they are related to a construction is obvious, as the find group comprises as different objects as a sea urchin and an infant! Whereas the first should probably be considered an amulet, human sacrifices are traditionally considered a far more radical and ultimate act, and thus a sacrifice concerning a wider circle than the individual household. The highly varied sacrifice material causes the traditional link between construction sacrifices and an extremely narrow celebrant group to be reassessed. The excavations at Nr. Tranders also stress the fact that the amount of registered construction sacrifices are highly dependant on the preservation conditions and context registration as well as an open mind towards ritual interpretations in a traditionally secular research setting. In 114 cases, it was possible to determine settlement sacrifices at Nr. Tranders (cf. Fig. 16). The variation between the sacrificed objects closely follows the above described construction sacrifice and bog sacrifice traditions – both as regards temporary intensity in the centuries around the birth of Christ and which objects were deposited. From a superior view, the settlement sacrifices are characterized by often having been deposited in small, independent sacrificial pits, which were merely dug down a few centimetres from the surface level of the time, and rarely more than 25 cm. This very limited deposition depth emphasizes the enormous problems and distorting factors, which are probably the reason why the settlement sacrifices are so anonymous in most Iron Age settlements. They were simply ploughed away! The dominating sacrificial animal in the settlements was the sheep, often a lamb. However, the dog, the horse, and the cow also occur frequently in the material, whereas the pig is rarely included in the finds. To judge from both settlement and structure sacrifices, the distribution of sacrificial animals seem to be a direct mirror image of the life basis of the Early Iron Age society in the Aalborg area. One ritual element in particular, however, fundamentally separates the group of settlement sacrifices from those connected to structures, namely fire. Whereas fire does not seem to be part of the ritual make-up concerning structure sacrifices, both burnt and unburnt sacrifices appear in the settlement sacrifice material (cf. Fig. 17 & 18). This condition is especially obvious when examining the deposited animal and human bones. The two maps on Fig. 19 show the finds of burnt and unburnt bone deposits respectively. On the background of these two plots (x, y, and z coordinates) the following analysis has been made: (interpolation “unburnt”)-(interpolation “burnt”), cf. Fig. 20. The analysis clearly points out that the relation between burnt and unburnt bone deposits is time related: the burnt deposits were made in the time before the birth of Christ, whereas the unburnt deposits were made during the following centuries. If this is related to the contemporary development of the grave custom in North Jutland, it is noteworthy that we can establish an obvious parallel development. Thus, the burial custom also changes around the beginning of the birth of Christ from a cremation grave custom to an inhumation grave custom. This coincidence probably indicates that within the two different religious and ritual contexts, the “ritual language” is to some degree identical when it comes to passing on humans and sacrificial animals. Irrespective of the superior sacrificial context – a bog, a lake, a field, a meadow, a structure, or a settlement – both the sacrifice intensity and the sacrificed objects seem to be based on objects from the daily household. As shown in the case of Nr. Tranders, the sacrifices occur in such large numbers on settlements with optimal preservation conditions that it is impossible to maintain the thesis that the Iron Age people had an especially one-sided preference for performing the sacrificial rituals in connection with wetland areas. As a supplement to the archaeological evidence, archaeologists have often sought support in historical accounts written by Romans in the centuries around the birth of Christ. The Roman historian Tacitus’ description of the religious activities of the Teutons is particularly describing and geographically differentiated. He mentions some general features such as the Teutons mainly worshipping Mercury (Mercury is the god of fertility, shepherds, etc.) and that they consider it a sacred duty even to bring him a human sacrifice on fixed days (i.e. a sacrifice cycle). Hercules and Mars (gods of strength and war) can only be reconciled with the allowed animal sacrifices. Besides, the Teutons consider it incompatible with the grandness of the heavenly powers to close them in behind walls and give them human features (cf. the lacking iconography). Tacitus´ overall description of the religion of the Teutons is thus primarily dealing with fertility sacrifices in relation to Mercury and the sacrifice of humans on certain days, i.e. a sacrifice cycle. More specifically, Tacitus describes the religious practice performed by tribes in South Scandinavia and North Germany at the time immediately succeeding the birth of Christ: “Nor in one of these nations does aught remarkable occur, only that they universally join in the worship of Nerthus; that is to say, the Mother Earth [Nerthus is phonetically concordant with the name Njord, a fertility goddess known from Norse mythology]. Her they believe to interpose in the affairs of man, and to visit countries. In an island of the ocean stands the wood Castum: in it is a chariot dedicated to the Goddess, covered over with a curtain, and permitted to be touched by none but the Priest. Whenever the Goddess enters this her holy vehicle, he perceives her; and with profound veneration attends the motion of the chariot, which is always drawn by yoked cows. Then it is that days of rejoicing always ensue, and in all places whatsoever which she descends to honour with a visit and her company, feasts and recreation abound. They go not to war; they touch no arms; fast laid up is every hostile weapon; peace and repose are then only known, then only beloved, till to the temple the same priest reconducts the Goddess when well tired with the conversation of mortal beings. Anon the chariot is washed and purified in a secret lake, as also the curtains; nay, the Deity herself too, if you choose to believe it. In this office it is slaves who minister, and they are forthwith doomed to be swallowed up in the same lake. Hence all men are possessed with mysterious terror; as well as with a holy ignorance what that must be, which none see but such as are immediately to perish.” Traditionally, the text is solely related to the numerous bog finds from the period. The question is, however, whether this is appropriate? Even a very limited analysis of the content of the text clearly reveals that the described religious exertion and the traces it must have left in the archaeological material can only be partly described from the numerous sacrificial bogs. The account of Nerthus may be split into two separate parts. One part that describes the common religious actions and another part comprising rituals carried out by a narrower group of people. The ritual mentioned with a severely limited circle (priest and slaves) comprises the washing of the goddess’ chariot by a lake and the succeeding sacrifice of the slaves chosen for the task. Far larger does the participant group appear throughout the rest of the Nerthus story. At first, there is a short mentioning of Nerthus driving about to the different tribes! This may be interpreted in such a way that the rituals described comprise actions, which take place where people are primarily moving about, i.e. in the villages! Perhaps the larger settlements of the Early Iron Age play a central part in relation to such common society-supporting ritual traditions. Tacitus decribes the physical context to be able to change its rules and norms at this sudden religious activity (cf. “They go not to war; they touch no arms.”) and in this way change sphere from an everyday, secular context to a religious context – a sacrosanct condition arises. The settlement thus enters different spheres at different times! Tacitus´ account of the execution of and the setting for the practiced ritual structure thus closely follows the structure known from archaeological excavations of bogs and settlements. How, then, does the religious practice of the Early Iron Age – and its sacrificial part in particular – appear on the background of the analyses above? (Fig. 22). May the sacrificial activity in actual fact be divided into two overriding groups, as was previously the tradition – individual structure sacrifices on settlements and both common and individual sacrifices in wetland areas – or is it necessary to revise and differentiate this view of Early Iron Age religion and the sacrificial customs in particular? The very unbalanced picture of the ritual displays of the society, involving chosen bogs as an almost “church-like” forum, is neither expressed in the archaeological material nor in the few written sources. On the contrary, the sacrificial activity appears as a very complex area, completely connected to the time and the regional development of the society of which it was part. Sacrificial objects primarily comprising everyday objects in the form of food, earthenware, animals, and humans did not differ from the secular culture until the actual ritual act took place. Considering the fact that the sacrificial objects comprised a wide range of everyday items, it is perhaps not so strange that the context in which the objects were sacrificed also varied considerably. It thus seems as if the conventional sacrificial customs were attached to the complete active resource area of the settlements, both in the form of wetland areas, and to the same degree of settlements. The conditions concerning burial sites, field systems, grazing areas, border markings, etc. still appear unclear, although it can be established that here, too, ritual activities took place according to the same conventions. The exertion of the rituals constituted a just as varied picture during the Early Iron Age as did the choice of sacrificial objects and place of sacrifice. Thus, we see objects deposited intact, as pars pro toto, smashed, burnt, etc. In spite of this very complex picture, patterns do seem to occur. There are thus strong indications that the rituals connected to settlement sacrifices of humans and animals during the Early Iron Age are closely connected with the rituals attached to the burial custom, and as such mirror a conventional communication form between humans and gods. Conversely, it seems as if structure sacrifices through all of the Early Iron Age primarily occur unburnt and that the ritual make-up connected to the finds of structure sacrifices is thus detached from the previously mentioned types of sacrifice, whereas the actual selection of the sacrificial objects seem to follow the same pattern. It is a characteristic of the ritual environments of the Early Iron Age that they appear momentary and as part of the daily life in the peasant community. Much thus indicates that permanent sacred environments and buildings did not exist to any particularly large degree. This does not imply that people would not return to the same sacred sacrificial places but rather that in between the sacrifices, these places formed part of the daily life, just as all the other parts of the cultural landscape. The examination of both published and unpublished material shows that the settlements were parallel contexts to the wetland areas and that these two contexts probably supplemented each other within the religious landscape of the Early Iron Age. In the light of the sacrificial find material there is no need to make a strong distinction between the religious societal roles of the settlements as opposed to the wetlands. The context (wetland and settlement) cannot in itself be understood as a useful parameter for determining whether we are dealing with large collective society-supporting ritual sites or sites connected to a minor village community. The question is whether the variation of sacrificial contexts should be related to different deities and myths, i.e. the mythical and narrative dimension of the religion, rather than to the size of the group of participants. On a few settlements, metal vessels, chariots, and humans were sacrificed – find types that are traditionally associated with the bogs and with groups of participants from a larger area than the individual settlement. This interpretation should also be applied to the settlements. In spite of the fact that from an overall perspective, the practiced religion in South Scandinavia seems homogenous, there is neither archaeological nor historical evidence for the presence of real ritual and religious units comprising large areas, such as complete provinces. However, we must assume that sacrifices of for instance humans, chariots, cauldrons, and the large weapon accumulations were made by groups of people exceeding the number of inhabitants in a single settlement. We thus have no reason for questioning the traditional concept that chosen wetland areas functioned as sacred places from time to time to major sections of the population – whether the sacrifices were brought about by for instance acts of war or as part of a cyclic ritual. The question is whether the large settlements of the Early Iron Age did not play a similar part to a hinterland consisting of a number of minor settlements, as the comprehensive finds from for instance the settlement mounds near Aalborg seem to indicate. During the Late Roman Iron Age and Early Germanic Iron Age, the previously so comprehensive sacrificial activity connected to the wetlands declined considerably. Parallel to this, the frequent settlement-related fertility sacrifices of bones and earthenware vessels in the Early Iron Age recede into the background in favour of knives, lances, craftsmen’s tools, and prestigious items representing the changed society of these centuries. During the Late Iron Age, the iconographic imagery, after having been throttled down for almost a millennia, regains a central role within the religion. This happens by virtue of a varied imagery on prestigious items such as bracteates and “guldgubber,” cf. Fig. 21. Seen as a whole, it seems as if – parallel to the development of the society during the Late Roman Iron Age and the Early Germanic Iron Age – there is a dimension displacement within the ritual and religious world, which manifests itself in an increased focus on the material dimension. The question is whether this very dimension displacement is not reflecting the religious development from the fertility-related Vanir faith to the more elitist Æsir faith. Jesper Hansen Odense Bys Museer Translated by Annette Lerche Trolle